2016
DOI: 10.3390/e18090322
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Fault Diagnosis of High Voltage Circuit Breakers with Unknown Fault Type Using Hybrid Classifier Based on LMD and Time Segmentation Energy Entropy

Abstract: Abstract:In order to improve the identification accuracy of the high voltage circuit breakers' (HVCBs) mechanical fault types without training samples, a novel mechanical fault diagnosis method of HVCBs using a hybrid classifier constructed with Support Vector Data Description (SVDD) and fuzzy c-means (FCM) clustering method based on Local Mean Decomposition (LMD) and time segmentation energy entropy (TSEE) is proposed. Firstly, LMD is used to decompose nonlinear and non-stationary vibration signals of HVCBs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…Runde et al [2] demonstrated through an extensive HVCB diagnostic test that vibration analysis is a suitable and reliable noninvasive diagnostic method for HVCBs. Analysis of HVCB vibration signals collected by acceleration sensor has been widely used in the state detection and fault diagnosis of HVCBs [3,4,5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Runde et al [2] demonstrated through an extensive HVCB diagnostic test that vibration analysis is a suitable and reliable noninvasive diagnostic method for HVCBs. Analysis of HVCB vibration signals collected by acceleration sensor has been widely used in the state detection and fault diagnosis of HVCBs [3,4,5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…The signal acquisition equipment must have a high sampling rate. An acceleration sensor has high accuracy, wide frequency and amplitude responses, small size, and is easy to install; thus, it is widely used in vibration data acquisition [3,4,5,6,7,8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, vibration diagnosis is suitable for the mechanical condition monitoring of high voltage CB [4,5]. In some recent years, researchers have done a lot of work in these fields.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of the HVCB is caused by several types of stress and aging, such as mechanical maladjustment, switching arcs erosion, and insulation level decline. The existing literature covers a wide range of specific countermeasures, including mechanism dynamic features [8][9][10], dynamic contact resistance [11], partial discharge signal [12,13], decomposition gas [14], vibration [15], and spectroscopic monitoring [16]. Furthermore, numerous studies applied neural networks [8], support vector machine (SVM) [17], fuzzy logic [18], and other methods [19], to introduce more automation and intelligence into the signal analysis.…”
Section: Introductionmentioning
confidence: 99%